1981
DOI: 10.1007/bf00056262
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal correlations of specific leaf weight to net photosynthesis and dark respiration of apple leaves

Abstract: Specific leaf weight (SLW), net photosynthesis (P n ), and dark respiration (R d ) of apple leaves were monitored for an entire growing season. Leaves were sampled from the canopy interior and periphery to provide a range of SLW. Leaf P n was linearly correlated with SLW until mid-August, when P n began to decline. During September the relationship between SLW and P n was a quadratic. Leaf R d and SLW were linearly correlated throughout the season. Leaf P n and R d were significantly correlated through most of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
8
0

Year Published

1985
1985
2021
2021

Publication Types

Select...
6
2
1

Relationship

2
7

Authors

Journals

citations
Cited by 26 publications
(16 citation statements)
references
References 11 publications
8
8
0
Order By: Relevance
“…It has been proven that girdling reduced maximal quantum yield of PSII photochemistry (Fv/Fm) (Nebauer et al 2011) and extremely few leaves results in a lower value of PN (Quentin et al 2013). Similar to other reports (Marini and Barden 1981, Thompson et al 1996, Jumrani et al 2017, the PN measured in the present study was positively correlated with SLM (Table 2), which is an important index of leaf development. The reduction in the PN of shoots with low LFRs (2L:3F and 1L:3F), along with the low Chl content and SLM values indicated that girdled shoots with extremely few leaves produced insufficient photosynthetic products to meet both their own requirement and a high fruit load, and that girdling blocked the transport of organic nutrients from other parts to the girdled shoot.…”
Section: Discussionsupporting
confidence: 90%
“…It has been proven that girdling reduced maximal quantum yield of PSII photochemistry (Fv/Fm) (Nebauer et al 2011) and extremely few leaves results in a lower value of PN (Quentin et al 2013). Similar to other reports (Marini and Barden 1981, Thompson et al 1996, Jumrani et al 2017, the PN measured in the present study was positively correlated with SLM (Table 2), which is an important index of leaf development. The reduction in the PN of shoots with low LFRs (2L:3F and 1L:3F), along with the low Chl content and SLM values indicated that girdled shoots with extremely few leaves produced insufficient photosynthetic products to meet both their own requirement and a high fruit load, and that girdling blocked the transport of organic nutrients from other parts to the girdled shoot.…”
Section: Discussionsupporting
confidence: 90%
“…Previous studies with many plant species demonstrated that leaves grown in a low-light environment were thinner and larger, with lower SLW and a thinner, poorly developed palisade layer, while leaves from a highlight environment were thicker and smaller, with higher SLW and a thicker, well-developed palisade layer (Chabot and Chabot, 1977;Fails et al 1982a;Jackson and Palmer, 1977;Mahall and Schlesinger, 1982;Wooge and Barden, 1987). Seasonal trends and values of SLW were similar to those previously re-ported for apple (Marini and Barden, 1981;Porpiglia and Barden, 1980). Marini and Barden (1981) reported that SLW was correlated with Pn potential throughout the season (R 2 ≥ 0.49), with the poorest relationships early and late in the season.…”
Section: Discussionsupporting
confidence: 86%
“…Seasonal trends and values of SLW were similar to those previously re-ported for apple (Marini and Barden, 1981;Porpiglia and Barden, 1980). Marini and Barden (1981) reported that SLW was correlated with Pn potential throughout the season (R 2 ≥ 0.49), with the poorest relationships early and late in the season. Rd rates and trends throughout the season were similar to those previously reported for apple (Marini and Barden, 1981;Porpiglia and Barden, 1980).…”
Section: Discussionsupporting
confidence: 86%
“…Chabot and Chabot (1977) detected increases in leaf thickness and SLW under high light conditions, and suggested that the observed leaf thickening was related to increases in mesophyll cell size and amounts of mesophyll tissue. Furthermore, a positive correlation between SLW and net photosynthesis was observed in apple and strawberry (Chabot and Chabot, 1977;Marini and Barden, 1981). We thus conclude that the higher SLW values observed in our study under LED were a consequence of leaf thickening, which was due to the increased accumulation of assimilation products occurring during accelerated leaf photosynthesis.…”
Section: Resultssupporting
confidence: 62%